ڕۆڵی ئینستاگرام لە ئاڕاستەکردنی پەیوەندییە کۆمەڵایەتییەکانی گەنجان لە هەرێمی کوردستاندا: توێژینەوەیەکی مەیدانییە - موڕاد, پ. د. هێرش رەسوڵ; ئەحمەد, جوان ئەسعەد (Sulaimani Journal for Humanities, 2023)
Instagram is a new paradigm in social media platforms that is an important way to communicate, according to the indications, most of the users are young people, which has experienced rapid progress since 2010. Participants can easily benefit from its services, including photos, videos, messages, use different filters, and cooperate in services with family members, relatives, and friends. This research believes that the role of Instagram is useful in guiding the social ties of youth in the Kurdistan Region, meaning family ties, relatives, and friendships. This type of relationship in social networks is a new trend of communication nowadays which may be a source of rebuilding or changing the direction of direct and real relationships. In terms of types, the research is a descriptive research that used the survey method to reach its objectives, the search tool is a new communication tool, especially Instagram, and its use in the Kurdistan Region. Its mission is the Kurdish youth in the Kurdistan Region, numbering 421 young people from the age of 16 to 40. The research has come up with some results, that the Instagram friendship connection is one of the most used types of links Writing services have the largest number of users. Young people, thanks to Instagram, exchange news and information and make it a tool to spend time with. Until now, among the youth of the Kurdistan Region, conditional relationships have not replaced face-to-face relationships, although they have taken successive steps in this aspect.
Keywords: role; Instagram; direction; social ties; youth; Iraqi Kurdistan Region